Perlindungan Hukum Terhadap Korban Kekerasan Seksual Terhadap Anak Dibawah Umur UU No. 35 Tahun 2014 Di Kota Bogor - Daffa Ramadhan; Achmad Asy’ari Abdullah Toran; Anisha Nabila; Jihan Khoirunnisa; Herli Antoni (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Children are God's creations that must be protected each because of their limitations. Protected one of which is the legal protection of children to accept a kind of violence. Accepting child violence has a negative impact on the child's future. Writing this to determine the need for protection in the Child Victims of Violence Act and legal protection for child victims of violence in accordance with legal regulations. Therefore, the State provides legal protection, all children are bound by law number 31 of 2014 concerning amendments to law No. 13 of 2006 concerning child and victim protection number 35 of 2014 to prevent violence against children.